BoLA-DRB3 polymorphism and their association with milk production traits in Indian cattle breeds - Hitesh Lamba,; Deepak Sharma,; Satyendra Pal Singh,; Madhu Tiwari,; Rakesh Goel,; Vijay Pandey,; Sanjeev Kumar Singh, (Journal of Livestock Biodiversity, 2025)
The present study was undertaken to investigate the polymorphism in DRB3 gene in Indian cattle breeds using PCR-RFLP assay. Amplification of 100 DNA samples of Sahiwal and Hariana breeds revealed 304 bp products using specific primer pairs. These amplicons were digested using Hae III restriction enzyme. It produced five genotypic patterns viz., AA genotype (170, 82 and 52 bp); BB genotype (222 and 82 bp), EE genotype (170 & 134 bp), heterozygous AB genotype (222, 170, 82 and 52 bp bands) and BD genotype (222, 193, 82 and 29 bp bands). AA genotype was the most frequent among all the screened cattle, followed by the AB, EE, BD and BBgenotypes. The frequency of DRB3/ Hae III A, B, D and E alleles were 0.660, 0.185, 0.035 and 0.120, respectively. Association study revealed no significant difference for milk production traits among all the DRB3 genotypes in first and second lactation except the dry period (DP), which had significant difference in second lactation. There was significant difference (P = 0.0106) for somatic cell count (SCC) among all the genotypes in screened Hariana cattle, while in sahiwal cattle no association was observed. This study needs further investigation on large population size with the incorporation of other breeds of Indian cattle.